REKONSTRUKSI HUKUM PERKAWINAN DIBAWAH TANGAN DALAM PERSPEKTIF FIQH BERDASARKAN NILAI KEMASLAHATAN - Munasir Munasir (UNISSULA, 2015)
Marriage is a physically and mentally bond between a man and a woman as husband and wife with the intention of forming a family or household happy and everlasting based on God. The dualism of the legal status of Islam in Indonesian society marriage is a problem that must be solved with emphasis on the value of the benefit. Methods used normative juridical method, this study sought to find out whether the law to be applied in order to solve a particular problem, in other words, normative juridical approach is the approach that examines the law asthe norm. The results obtained are 1. that the marriage Construction under the hand according to Islamic jurisprudence Islamic marriage between husband and wife with Moslem or nonMoslem with a harmonious marriage include the willingness and consent qobul. Marriage is said to be valid if carried out in accordance with Islamic fiqh with the five pillars of marriage,namely a) Approval of the bride and groom, b) Mayor of marriage, c) Two witnesses, d) Ijab qobul and d) Mahar. And reconstruction of marital law under the hand in the perspective ofIslamic jurisprudence by requiring that the benefit of legal marriage should Replaces, ie the agreement of both bride and groom, guardian of marriage, two witnesses, the dowry, consentqobul and please register at KUA / civil records.